The Influence of Using Big Book Learning Media on the Expressive Language Skills of 5-6 Year Old Children at TK Nusa Makassar - Sri Reski Ratmila; Herman Herman; Sri Rika Amriani H (EduLine: Journal of Education and Learning Innovation, 2024)
This study aims to determine the influence of Big Book learning media on the expressive language ability of 5-6 year old children at TK Nusa. The research approach used was quantitative with a Quasi Experimental Design. The population in this study was group B aged 5-6 years at TK Nusa Makassar, totaling 48 children. Purposive sampling technique was used to select a sample of 20 children from group B, with 10 children in the experimental group and 10 children in the control group. Data collection techniques included observation, tests, and documentation. Data analysis techniques used were descriptive statistical analysis and non-parametric analysis using Wilcoxon Signed Rank Test version 26. Based on the research results, it can be concluded that the expressive language ability of children treated with Big Book learning media in the experimental group was better compared to the control group. The average increase in the experimental group was 22.20, while in the control group it was 15.20. The test results showed Asymp. Sig. (2-tailed) 0.005 < 0.05, hence H0 was rejected and H1 was accepted. Therefore, it can be concluded that there is an influence of Big Book learning media on the expressive language ability of 5-6 year old children at TK Nusa Makassar.